2012
DOI: 10.1007/s11434-012-5547-7
|View full text |Cite
|
Sign up to set email alerts
|

A tree-ring-based reconstruction of the Yimin River annual runoff in the Hulun Buir region, Inner Mongolia, for the past 135 years

Abstract: Based on the relationships between the regional tree-ring chronology (RC) of moisture-sensitive Pinus sylvestris var. mongolica and the monthly mean maximum temperature, annual precipitation and annual runoff, a reconstruction of the runoff of the Yimin River was performed for the period 1868-2002. The model was stable and could explain 52.2% of the variance for the calibration period of . During the past 135 years, 21 extremely dry years and 19 extremely wet years occurred. These years represented 15.6% and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 43 publications
(77 reference statements)
0
10
0
Order By: Relevance
“…River flow variation is controlled by the climate and land use/ cover characteristics (Frans et al, 2013;Mishra et al, 2010;Wang et al, 2008). In some regions, it is also influenced by largescale climatic patterns associated with the teleconnections and the El Ni˜no-Southern Oscillation (ENSO) (Bao et al, 2012;Bates, et al, 2008;Davi et al, 2006). This research showed that precipitation has a stronger influence on the river flow than warming in the study area, which is categorized as semiarid region.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…River flow variation is controlled by the climate and land use/ cover characteristics (Frans et al, 2013;Mishra et al, 2010;Wang et al, 2008). In some regions, it is also influenced by largescale climatic patterns associated with the teleconnections and the El Ni˜no-Southern Oscillation (ENSO) (Bao et al, 2012;Bates, et al, 2008;Davi et al, 2006). This research showed that precipitation has a stronger influence on the river flow than warming in the study area, which is categorized as semiarid region.…”
Section: Discussionmentioning
confidence: 73%
“…The precipitation shows an insignificant trend during the long-term period ; however, it has a few cyclic variabilities (two wet and three dry periods) at within-decadal and multi-decadal time scales (Figure 2). Previous studies (Bao et al, 2012;Davi et al, 2006) showed that hydroclimate variations in the Selenge River Basin and in the west-central and northeastern Mongolian Plateau could respond to large-scale climate forcing, such as that resulting from the Pacific decadal oscillation (PDO), the ENSO, and sunspot activity. The Tuul River Basin is one of the headwater basins of the Selenge River Basin; therefore, the cyclic pattern of precipitation in the study area is likely to be associated with the above-mentioned phenomena.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Li et al (1994) developed the runoff field of the Yili area during the period 1818-1990 with Picea schrenkiana; Yuan et al (2007) presented the Manasi River streamflow variations from 1629 to 2000 using Picea schrenkiana; and Cook et al (2013) rebuilt Upper Indus River flow (May-September) from AD 1452 to 2008 with a multi-species tree-ring network from inside northern Pakistan. Based on tree-ring data from the source region, some streamflow reconstructions for the major rivers of Mongolia were developed (Pederson et al 2001;Bao et al 2012;Liu et al 2010;Davi et al 2013). These streamflow series make us understand the hydrologic variations of Central Asia better.…”
Section: Introductionmentioning
confidence: 99%
“…Among scientific researches about water resources, periodicity analysis is often seen, e.g., in studies about precipitation (Wang and Wang, 2002) and river runoff (Bao, Liu, and Liu, 2012;Dai et al, 2007;Fan et al, 2012;Li et al, 2006;Wang and Wang, 2002;Yuan et al, 2013) with one or more statistical methods (e.g., power spectral analysis and wavelet analysis). Among the methods for periodicity analysis, power spectral analysis is widely used in many fields of precipitation, river runoff, and climate .…”
Section: Introductionmentioning
confidence: 99%